Social media : the good, the bad, and the ugly : 15th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2016, Swansea, UK, September 13-15, 2016, Proceedings /: the good, the bad, and the ugly : 15th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2016, Swansea, UK, September 13-15, 2016, Proceedings. (2016) - Unknown
No abstract available